Awareness and attitude towards smoking in public places among general population in Guntur city - Ravoori, Srinivas; Yaddanapalli, Suresh Chand; Shaik, Parveen Sultana; Pavani, Nijampatnam P. M.; Kommineni, Harish Chowdary; Velagapudi, Dileep (International Journal Of Community Medicine And Public Health, 2020)
Background: This study determined to know the awareness and attitude towards the state prohibition of smoking in public places law. Methods: Descriptive cross-sectional study design. 400 consenting respondents recruited using a convenience sampling method were interviewed using a semi-structured questionnaire covering their smoking pattern, awareness and attitude towards the law of prohibition of smoking in public places in Guntur, Andhra Pradesh State. Data was analysed using descriptive, Chi-square and Pearson correlation. Results: About 95.3% of the participants agreed that they do not encourage smoking in public places and 99% of them supported the proposition that smoking in public places causes problems to others where 53.8% supports ban of tobacco and 92% of participants perceived that implementing laws can prevent smoking in public places. 83% of participants restrict a person smoking in public places and only 3.3% of participants are aware of the act done by the government. 74% of the participants stated that television is the prime source of information that is effective in preventing smoking in public places followed by radio (8.5%) and cinema halls (7.8%). Conclusions: There is poor awareness and attitude towards the law of prohibition of smoking in public places in Guntur. It is necessary to increase sensitization of the general public and enforcement of the COTPA act.